PENINGKATAN PENDAPATAN KELUARGA MELALUI USAHA KUE KERING DESA ARGOSARI JABUNG - Astuti, Tita Boedi; Poedjiastuti, Widanarni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Abstract: Partners in the Community Partnership Program (PKM) activities, namely Tuk'ah's mother pastry entrepreneurs who produce cookies on the basis of orders, except on holidays. The equipment used by Partners is very simple and many have been damaged, as well as a place to produce, therefore some equipment is needed in accordance with production capacity and some training both in managerial and product terms. Pastry entrepreneurs have high potential to be developed because pastries are one of the favorite cakes among all people and the marketing area is still around. This community service activity aims to increase production capacity and increase family income. The method applied in this partnership program is training, mentoring and monitoring so that partners continue to grow and be able to compete with similar businesses. The results of this community partnership program are procurement of tools to support the production process, improvement of production sites and training and assistance in making simple bookkeeping, marketing and entrepreneurship, training in variants of pastries. It is hoped that the PKM Program (Community Partnership Program) will be able to solve the problems faced by partners so that it will create a larger pastry business and increase family income. Keyward: microbusiness, pastries